Epithelial dysfunction in chronic respiratory diseases, a shared endotype?. Issue 1 (January 2020) - Steelant, Brecht
Abstract : Purpose of review: Epithelial barrier defects are being appreciated in various inflammatory disorders; however, causal underlying mechanisms are lacking. In this review, we describe the disruption of the airway epithelium with regard to upper and lower airway diseases, the role of epigenetic alterations underlying this process, and potential novel ways of interfering with dysfunctional epithelial barriers as a novel therapeutic approach. Recent findings: A defective epithelial barrier, impaired innate defence mechanisms or hampered epithelial cell renewal are found in upper and lower airway diseases. Barrier dysfunction might facilitate the entrance of foreign substances, initiating and facilitating the onset of disease. Latest data provided novel insights for possible involvement of epigenetic alterations induced by inflammation or other unknown mechanisms as a potential mechanism responsible for epithelial defects. Additionally, these mechanisms might precede disease development, and represent a novel therapeutic approach for restoring epithelial defects. Summary: A better understanding of the role of epigenetics in driving and maintaining epithelial defects in various inflammatory diseases, using state-of-the-art biology tools will be crucial in designing novel therapies to protect or reconstitute a defective airway epithelial barrier.